Research on the changes in the disease burden of nasopharyngeal carcinoma caused by global occupational formaldehyde exposure from 1990 to 2021 and prediction of future trends - Tingting Duan; Tingting Duan; Mengyao Qin; Yue Du; Derong Zhu; Xuejun Zhou; Shun Ding; Shun Ding; Desheng Wang (Frontiers in Public Health)
BackgroundExplore the changes in the burden of nasopharyngeal carcinoma (NPC) caused by occupational formaldehyde exposure from 1990 to 2021, and predict its development trend up to 2050, to provide references for formulating relevant policies and measures.MethodsUsing the Global Burden of Disease database 2021 (GBD 2021), we counted and analyzed the numbers and standardized rates of NPC deaths and disability–adjusted life years (DALYs) caused by occupational formaldehyde exposure globally, in 21 regions, and in 204 countries. Combined with correlation analysis, health inequality analysis, and frontier analysis, we further comprehensively described the disease burden and its changing trends. In addition, we used the Bayesian age–period–cohort model to predict the disease burden from 2022 to 2050.ResultsFrom 1990 to 2021 and from 2022 to 2050, the global disease burden of NPC caused by occupational formaldehyde exposure shows a downward trend. In terms of gender, the disease burden is higher among men than among women. From the perspective of the socio-demographic index (SDI), the disease burden is most severe in regions with lower SDI. Geographically, there are significant differences in the disease burden among different countries and regions, with South Asia, East Asia, and Africa having the highest disease burden. In addition, in terms of age distribution, the disease burden is relatively higher among middle-aged people, especially those aged 45–49.ConclusionsFrom 1990 to 2021, the disease burden of NPC caused by global occupational formaldehyde exposure showed a downward trend, and the regional burden decreased with the increase of SDI.